2020
DOI: 10.1186/s12909-020-02322-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplemental high Fidelity simulation training in medical students

Abstract: Background Simulation-based education (SBE) with high-fidelity simulation (HFS) offers medical students early exposure to the clinical environment, allowing development of clinical scenarios and management. We hypothesized that supplementation of standard pulmonary physiology curriculum with HFS would improve the performance of first-year medical students on written tests of pulmonary physiology. Methods This observational pilot study included SBE with three HFS scenarios of patient care that highlighted bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
1
6
1
2
Order By: Relevance
“…Padilha et al [ 14 ] describe the development of knowledge as influenced by both student’s intrinsic factors as well as extrinsic factors such as satisfaction. Our experience is in keeping with studies described in the literature including that by Meyers et al [ 15 ], an observational pilot study that showed supplemental simulation-based training using a high-fidelity manikin improved overall satisfaction in preclinical medical students.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Padilha et al [ 14 ] describe the development of knowledge as influenced by both student’s intrinsic factors as well as extrinsic factors such as satisfaction. Our experience is in keeping with studies described in the literature including that by Meyers et al [ 15 ], an observational pilot study that showed supplemental simulation-based training using a high-fidelity manikin improved overall satisfaction in preclinical medical students.…”
Section: Discussionsupporting
confidence: 86%
“…Limitations of the simulation technology also require consideration. In clinical practice, patients may present atypically, and a disadvantage of simulation-based bedside teaching is that these subtle nuisances and atypical presentations are not conveyed as well as when compared with a true patient presentation [ 15 ]. Simulation-based teaching may therefore not always represent a suitable alternative, particularly when there is advocation for preserving bedside teaching even in the face of new technologically assisted learning methods, with beliefs being held that nothing can simulate real patient encounters [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study corroborated other reports. Professional knowledge improved after the simulation, with the participants' scores being higher than values before simulation [9]. In a previous report, students who practiced with task variation did not outperform those who practiced repeatedly on the same task; in this study experience in myocardial infarction had no significant influence on knowledge improvement in asthma scenario [10,23].…”
Section: Discussioncontrasting
confidence: 55%
“…As mentioned in previous reports, there is no doubt about the benefits of SBT in learning asthma exacerbation, but whether more simulation-based training would be better is unknown [3,6,9]. It was demonstrated that students progress rapidly and acquire higher performance scores after practicing with different scenarios or repeatedly practicing on the same scenario [10].…”
Section: Introductionmentioning
confidence: 91%
“…"The technological advancements of the simulation devices along with the research in healthcare simulation in the last two decades have encouraged the implementation of simulation-based medical education (SBME) in the medical field" [6]. "High-fidelity patient simulators as part of the SBME provides great opportunities to medical students for early exposure to the clinical environment by imitating real-life clinical scenarios and learning their management in a safe environment" [7]. These guided and interactive experiences simulate real clinical settings that vastly support students' understanding of the relevant topics [8,9].…”
Section: Introductionmentioning
confidence: 99%